Comparison of the disc diffusion assay with spectrophotometer technique for antibacterial activity of diclofenac sodium, indomethacin and mefenamic acid - S AL-Janabi, Ali Abdul Hussein (Asian Journal of Pharmaceutics (AJP), 2014)
Non-steroidal anti-inflammatory drugs (NSAIDs) contain a wide range of effective drugs that use in treatment of inflammatory diseases. Chemical agents of non-steroidal anti-inflammatory drugs including diclofenac sodium, indomethacin and mefenamic acid, were screened for antibacterial activity by using two methods: Disc diffusion assay and spectrophotometer technique. From the results of disc diffusion method, Staphylococcus aureus exhibited susceptibility to diclofenac sodium and mefenamic acid. While, spectrophotometer method showed that Paracoocus yeei was susceptible to all tested compounds. Diclofenac sodium had loweress MIC (2.5 mg/ml) to inhibit all of seven isolated strains. The application of spectrophotometer technique in this study considers more suitable method than those of disc diffusion test to reveal antibacterial activities of tested agents, especially with indomethacin.